Tarjamat al-Aghani al-Indunisiyah Ila al-‘Arabiyah Ala Dhou’i al-Shoutiyyat al-‘Arabiyah - Firdaus, Rousul (Dzil Majaz: Journal of Arabic Literature, 2024)
With the widespread use of social media, particularly the YouTube platform, it has emerged as one of the most significant phenomena in the current digital landscape. It serves not only as a medium for sharing and accessing visual content but also as a space for various forms of creativity, innovation, invention, and information. Its extensive use is evident in the rapidly increasing amount of content covering diverse topics such as entertainment, product reviews, and education, including the delivery of learning materials, learning activities, instructional models, and even song translations from one language to another. The purpose of this study is to analyze errors in the translation of syllables (maqtha’) in Indonesian songs translated into Arabic on several YouTube channels. The approach used in this research is qualitative with a descriptive-analytical method. The main data sources are translated song lyrics from the channels “Kampung Arab Al-Azhar” and “Inspirasi Arabia”, both focusing on the same theme, namely “Mungkin”. Secondary sources include books, magazines, journals, and scholarly articles closely related to the topic. Data collection methods utilized include observation and documentation on one of the relevant YouTube channels. The research findings indicate that Arabic phonetics play a crucial role in translating Indonesian songs into Arabic to maintain the beauty of the target language by ensuring syllable harmony between the source and target languages.